(untitled) (Bangladesh Journal of Medical Science, 2021)
Lipoma is a benign mesenchymal tumour of adipose tissue and relatively rare occurrence in head and neck area. Mostly lipoma have a diameter of 2 cm and rarely grow beyond 10 cm. However, it may occasionally enlarge rapidly and become huge to become a giant lipoma which measures at least more than 10 cm in one dimension or weighing at least 1000g. The presentation of the anterior neck swelling is mostly related to the thyroid gland. However, it also can be the other soft tissue swellings, such as lipoma, which is the commonest mesenchymal tumours in adults. The lipomas however, are commonly involving the head and posterior neck region, which estimate about 15-20% of the cases and mostly small. We present the case of a 80-yearold man with huge anterior neck swelling for thirty years. The complete excision was performed with a good post-operative healing and cosmesis. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.449-452